Design guide for cool thermal storage - Glazer, Jason, 1966- (ASHRAE, 2019)
"The second edition of this guide provides design guidance for cool thermal storage solutions. The guide compares different types of storage, particularly ice and chilled-water storage, and walks practitioners through every step in the design process from project initiation to commissioning and occupancy"--